مجالات التربية الصحية في محتوى كتب العلوم بالتعليم الأساسي في سلطنة عمان: دراسة تحليلية - Sulaiman Al-Haji, S.S.; Ab. Rahman, A. (Universiti Sains Islam Malaysia, 2024)
The purpose of this analytical study; disclosure the extent of how much the basic education science books contain the health areas that should be included. This is confirmed by the annual health report of the Ministry of Health (2002a) in the Sultanate of Oman. The study sample consisted of science textbooks for grades fifth through eighth. The researcher prepared a list including (82) points of health education aspects, to be included in the science books content, the list includes: personal health, health nutrition, preventive education, environmental health and disease prevention. From the references, studies and the objectives of the science subjects that was arbitrated by a group of experts in the fields of education and health. In the light of this list, the researcher prepared the content analysis card, and considered the paragraph a unit of analysis. The study revealed that: The science books contained (37%) of the health education. These areas were not subject to horizontal and vertical integration criteria. Health content has focused on the first area of personal health, focusing on aspects: structural, functional and sometimes linked to health aspects. The study recommended that health education should be given greater attention when preparing science textbooks.